Images of Exclusion in Shinsei Kamattechan’s Work: Bullying, Hikikomori, Unemployment, Mental Illness, Gender Non-conformity in Contemporary Japan - Monkiewicz , Błażej (Silva Iaponicarum, 2024)
In this article, the author focuses on the contemporary Japanese music band, Shinsei Kamattechan 神聖かまってちゃん. The band’s songwriter, who goes by the artistic pseudonym of “Noko” (の子), seems to base their (they are non-binary) oeuvre on their own experiences of being bullied and excluded, as well as that of suffering from mental illness, suicidal thoughts, and unemployment. These experiences found in Kamattechan’s work can be called “images of exclusion”. The aim of this paper is to present the aforementioned images of exclusion in a broader sociological context. To do that, the article analyses the band’s songs in a broader perspective based on the academic literature on the topic of Heisei Japan (1989–2019). The paper concludes by providing evidence that his family’s origin was as a Heisei era hi-shimin (非市民; people excluded from the norm) from the start, with Noko’s father being part of the “working poor”. Various social problems of Heisei-era Japan (for example bullying or hikikomori 引きこもり) are clearly reflected in Noko’s biography and closely intertwined with their art.